Water stratification in the marine biome restricts vertical environmental DNA (eDNA) signal dispersal. Issue 1 (13th November 2019) - Jeunen, Gert‐Jan; Lamare, Miles D.; Knapp, Michael; Spencer, Hamish G.; Taylor, Helen R.; Stat, Michael; Bunce, Michael; Gemmell, Neil J.
Abstract: Background: The utility of environmental DNA (eDNA) metabarcoding surveys to accurately detect species depends on the degree of DNA dispersal. Multiple marine studies have observed only minimal eDNA transport by horizontal water movement across small spatial scales, leading to the conclusion that spatially specific eDNA signals accurately resemble in‐field species assemblages along a horizontal axis. Marine communities, however, are also structured vertically according to depth. In marine environments displaying permanent water stratification, vertical zonation patterns may be more apparent and present on smaller spatial scales (i.e., meters) than horizontal community structuring. The scale at which eDNA signals differ along a vertical transect and the accuracy of eDNA metabarcoding in revealing naturally stratified communities have yet to be assessed. Methods and results: In this study, we determined the ability of eDNA metabarcoding surveys to distinguish vertically localized community assemblages. To test this, we sampled three vertical transects along a steep rock wall at three depths (0 m, 4 m, 15 m), covering two distinct communities that were separated by near‐permanent water column stratification in the form of a strong halocline at 3 m. Using three metabarcoding assays, our eDNA metabarcoding survey detected 54 taxa, across 46 families and 7 phyla, including 19 fish, 15 crustacean, and 8 echinoderm species. Ordination and cluster analyses show distinct eDNA signals across the halocline for all three replicate transects, suggesting that vertical dispersal of eDNA between communities was limited. Furthermore, eDNA signals of individual taxa were only retrieved within their observed vertical distribution, providing biological validation for the obtained results. Our results demonstrate, for the first time, the need to take into consideration oceanographic (e.g. water column stratification) and biological processes (e.g. vertical community structuring) when designing sampling strategies for marine eDNA metabarcoding surveys. Abstract : In this study, we determined the ability of eDNA metabarcoding surveys to distinguish vertically localized community assemblages. Our results demonstrate, for the first time, the need to take into consideration oceanographic (e.g., water column stratification) and biological processes (e.g., vertical community structuring) when designing sampling strategies for marine eDNA metabarcoding surveys.